Carbon compatible binder for silicon-carbon negative electrode of lithium ion battery as well as preparation method and application of carbon compatible binder
By adopting the carbon-compatible binder CMC-Py, the performance problems caused by the volume changes of the silicon carbon anode material of lithium-ion batteries are solved, and good interface compatibility with silicon carbon materials is achieved, which significantly improves the cycle stability and rate performance of the battery. .
Patent Information
- Application Number
- CN202411409821.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Due to volume changes in existing lithium-ion batteries, the battery cycle stability and rate performance are poor, and commonly used binders are difficult to compatible with the interface of silicon-carbon materials, resulting in the extreme sheet being easily powder-lossed.
The carbon-compatible binder CMC-Py is used. This binder is amidated by sodium carboxymethylcellulose and 1-pyrene methylamine hydrochloride. The synthetic binder has good carbon compatibility and can be effective. Improve interface compatibility with silicon-carbon materials.
It significantly improves the electrochemical performance of silicon carbon anode of lithium-ion batteries, including improving cycle stability and rate performance, reducing the phenomenon of powder loss of the electrode sheet, and the synthesis process is simple, low-cost and environmentally friendly.
Smart Images

Figure CN119463738A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a carbon-compatible binder for a silicon-carbon negative electrode of a lithium ion battery, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in commercial products such as mobile phones, laptops, digital cameras, and new energy vehicles due to their high energy density, high operating voltage, low self-discharge rate, and no memory effect. In the application of lithium-ion battery negative electrode materials, silicon has a very high theoretical specific capacity (4200mAh g -1 ), which is much higher than the theoretical specific capacity of commercial graphite (372 mAh g -1 ), is considered to be the most promising next-generation negative electrode material. However, silicon as a negative electrode material undergoes a huge volume change during the process of lithium insertion and extraction, which seriously hinders its commercialization. Compared with silicon, silicon-carbon has better cycle performance and higher coulombic efficiency, and is currently a hot spot for the commercialization of silicon-based materials. However, silicon-carbon materials still have a large volume change problem, resulting in poor battery cycle stability and rate performance.
[0003] At present, the main methods to solve the volume change problem of silicon-carbon negative electrodes include nano-sizing, composite and structuring. However, these methods have complex synthesis steps and high costs, making them difficult to commercialize. In contrast, it is more economical and effective to improve the performance of silicon-carbon negative electrodes by improving binders. Although binders account for a small proportion of electrode materials, usually less than 10%, they are an extremely important component in the electrode structure of lithium-ion batteries and have a huge impact on the performance of batteries. Currently, commonly used negative electrode binders such as PAA and CMC / SBR are difficult to disperse silicon-carbon materials evenly during the pulping process. This is mainly because the structure of silicon-carbon materials is relatively complex and contains more carbon. These conventional binders do not contain carbon-philic groups, resulting in interfacial incompatibility with carbon, causing the pole pieces to easily fall off. Therefore, conventional binders are not currently suitable for silicon-carbon negative electrodes. Summary of the invention
[0004] Based on the problems existing in the above background technology, the present invention provides a carbon-compatible binder for a silicon-carbon negative electrode of a lithium-ion battery.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned carbon-compatible binder for the silicon-carbon negative electrode of a lithium-ion battery.
[0006] Another object of the present invention is to provide application of the above carbon-compatible binder.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A carbon-compatible binder for silicon-carbon negative electrode of lithium-ion battery is abbreviated as CMC-Py. It is prepared by dissolving sodium carboxymethyl cellulose in phosphate buffer solution, then adding N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide to activate the carboxyl group of sodium carboxymethyl cellulose, and finally adding 1-pyrenemethylamine hydrochloride, and reacting under N2 stirring at room temperature.
[0009] Preferably, the molar ratio of the sodium carboxymethyl cellulose and 1-pyrenemethylamine hydrochloride in the 1-pyrenemethylamine hydrochloride solution is (2-4):1; the concentration of the 1-pyrenemethylamine hydrochloride solution is 0.01-0.04 gmL; the sodium carboxymethyl cellulose is 1-2 wt% of the phosphate buffer solution; the molar ratio of the sodium carboxymethyl cellulose to the total molar ratio of N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is (1-2):1.
[0010] Preferably, the pH of the phosphate buffer solution is 5 to 6, and the reaction time is 6 to 12 hours.
[0011] Preferably, the mass ratio of the N-hydroxysuccinimide to 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1:1.
[0012] The method for preparing the carbon-compatible binder for the silicon-carbon negative electrode of a lithium-ion battery comprises the following steps:
[0013] S1. dissolving sodium carboxymethyl cellulose in phosphate buffer solution, and then adding N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide to activate the carboxyl group of sodium carboxymethyl cellulose;
[0014] S2. Then, 1-pyrenemethylamine hydrochloride is added to step S1, and the mixture is stirred and reacted under N2 flow at room temperature to obtain a carbon-compatible binder.
[0015] A negative electrode is prepared by mixing active material silicon carbon, a conductive agent and the carbon compatible binder, dissolving them with deionized water, coating them on copper foil after fully mixing them evenly, and vacuum drying them.
[0016] Preferably, the conductive agent is one or more of conductive carbon black, carbon nanotubes, special conductive carbon black or conductive graphite; the mass ratio of the active material silicon carbon, the conductive agent and the carbon compatible binder is (7-8):(1-2):1; the vacuum drying temperature is 60-100°C, and the vacuum drying time is 10-16h.
[0017] The negative electrode is used in a lithium ion battery.
[0018] Preferably, the negative electrode material of the lithium-ion battery is a silicon-carbon composite material.
[0019] The present invention uses sodium carboxymethyl cellulose as the main chain to undergo an amidation reaction with 1-pyrenemethylamine hydrochloride to synthesize a carbon-compatible binder. Among them, sodium carboxymethyl cellulose is a carboxymethylated derivative of cellulose and is the most important ionic cellulose gum. Sodium carboxymethyl cellulose is usually an anionic polymer compound prepared by reacting natural cellulose with caustic soda and monochloroacetic acid, and its molecular weight ranges from several thousand to one million. Sodium carboxymethyl cellulose is a white fibrous or granular powder, which is odorless, tasteless, hygroscopic, and easy to disperse in water to form a transparent colloidal solution. The pyrene group in the binder can form π-π conjugation with graphite in the silicon-carbon material, which can effectively improve the interface compatibility between the binder and the silicon-carbon material, enhance the dispersibility and adhesion to the silicon-carbon material, and thus significantly improve the electrochemical performance of the silicon-carbon negative electrode of the lithium-ion battery.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The carbon-compatible binder CMC-Py of the present invention has good interface compatibility with graphite and silicon negative electrode materials. It is prepared by amidation reaction of sodium carboxymethyl cellulose as the main chain with 1-pyrenemethylamine hydrochloride, and has good interface compatibility with graphite, conductive carbon black and silicon materials. This is because sodium carboxymethyl cellulose contains a large number of hydroxyl groups, which can form hydrogen bonds with oxygen-containing functional groups on the silicon surface. At the same time, the introduced pyrene groups contain a large number of benzene ring functional groups, which are similar to the graphite structure and can form π-π conjugation.
[0022] 2. The CMC-Py carbon-compatible binder prepared by the present invention is an aqueous binder, which has the advantages of being easily soluble in water, having good dispersibility and strong adhesion to silicon-carbon materials, and can effectively improve the interface compatibility between the binder and silicon-carbon materials, and enhance the dispersibility and adhesion to silicon-carbon materials; at the same time, it has electrochemical stability, which is beneficial to improving the long-cycle stability of the silicon-carbon negative electrode of the lithium-ion battery, and significantly improves the electrochemical performance of the silicon-carbon negative electrode of the lithium-ion battery.
[0023] 3. The present invention has the advantages of simple synthesis process, low cost and environmental friendliness, and is easy to apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The cycling performance of the CR2032 button cell assembled in Example 1 at a current density of 0.3C.
[0025] Figure 2 The cycle performance of the CR2032 button batteries assembled in Example 1 and Comparative Example 1 respectively. DETAILED DESCRIPTION
[0026] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0027] Example 1
[0028] 0.5 g of sodium carboxymethyl cellulose (CMC) was dissolved in 50 mL of phosphate buffer solution (PBS, pH = 5.0), and then 0.0594 g of N-hydroxysuccinimide and 0.099 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide were added to activate the carboxyl group of sodium carboxymethyl cellulose. After 30 minutes, 1-pyrenemethylamine hydrochloride solution (0.138 g of 1-pyrenemethylamine hydrochloride dissolved in 10 mL of methanol) was added dropwise, and N2 was stirred at room temperature for 9 hours, and then washed with ethanol to precipitate the product, which was filtered and freeze-dried for 12 hours to obtain carboxymethyl cellulose grafted pyrene powder, abbreviated as CMC-Py.
[0029] 2. Dissolve CMC-Py powder in deionized water to prepare a 5 wt% CMC-Py aqueous solution.
[0030] 3. Mix the active material silicon carbon, the conductive agent SuperP and the 5wt% CMC-Py aqueous solution in a mass ratio of 8:1:1, add 500μL of deionized water and stir in a degassing mixer to obtain a uniformly dispersed electrode slurry, apply the electrode slurry on a copper foil, vacuum dry at 80°C for 12h, and cut into a circular negative electrode sheet with a diameter of 14mm.
[0031] 4. Transfer the dried negative electrode sheet into a glove box filled with argon, use the lithium sheet as the counter electrode, and use the electrolyte at 1 mol L -1 LiPF6 was used as the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 as the solvent, 10wt% fluoroethylene carbonate (FEC) and 1wt% ethylene carbonate (VC) as additives, and assembled into a CR2032 button cell, abbreviated as SiC950@CMC-Py.
[0032] Figure 1 The cycle performance of the CR2032 button cell prepared in Example 1 at a current density of 0.3C. Figure 1 It can be seen that the CR2032 button cell composed of carbon compatible binder CMC-Py has a first discharge capacity of 1000mAh g at a current density of 0.3C. -1 The first coulombic efficiency is above 80%, and the capacity remains at 672 mAh g after 200 cycles. -1 , showing good cycle performance.
[0033] Example 2
[0034] 1. Dissolve 0.5g sodium carboxymethyl cellulose (CMC) in 50mL phosphate buffer solution (PBS, pH=5.0), then add 0.0594g N-hydroxysuccinimide and 0.099g 1-ethyl-(3-dimethylaminopropyl) carbodiimide to activate the carboxyl group of sodium carboxymethyl cellulose. After 30 minutes, add 1-pyrenemethylamine hydrochloride solution (0.276g 1-pyrenemethylamine hydrochloride dissolved in 10mL methanol) dropwise, stir and react for 9h at room temperature under N2, then wash with ethanol to precipitate the product, filter, and freeze-dry for 12h to obtain carboxymethyl cellulose grafted pyrene powder, abbreviated as CMC-Py.
[0035] 2. Dissolve CMC-Py powder in deionized water to prepare a 5 wt% CMC-Py aqueous solution.
[0036] 3. Mix the active material silicon carbon, the conductive agent SuperP and the 5wt% CMC-Py aqueous solution in a mass ratio of 8:1:1, add 500μL of deionized water and stir in a degassing mixer to obtain a uniformly dispersed electrode slurry, apply the electrode slurry on a copper foil, vacuum dry at 80°C for 12h, and cut into a circular negative electrode sheet with a diameter of 14mm.
[0037] 4. Transfer the dried negative electrode sheet into a glove box filled with argon, use the lithium sheet as the counter electrode, and use the electrolyte at 1 mol L -1 The CR2032 button cell was assembled with LiPF6 as the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 as the solvent, 10wt% fluoroethylene carbonate (FEC) and 1wt% ethylene carbonate (VC) as additives.
[0038] Comparative Example 1
[0039] 1. Dissolve sodium carboxymethyl cellulose powder in deionized water to prepare a 5 wt % sodium carboxymethyl cellulose aqueous solution.
[0040] 2. Mix the active material silicon carbon, the conductive agent SupperP and the 5wt% sodium carboxymethyl cellulose aqueous solution in a mass ratio of 8:1:1, add 500μL of deionized water and put it into a degassing mixer to stir to obtain a uniformly dispersed electrode slurry, apply the electrode slurry on the copper foil, vacuum dry it at 80℃ for 12h, and cut it into a circular negative electrode sheet with a diameter of 14mm.
[0041] 3. Transfer the dried negative electrode sheet into a glove box filled with argon, use the lithium sheet as the counter electrode, and use 1 mol L electrolyte. -1LiPF6 was used as the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 as the solvent, 10wt% fluoroethylene carbonate (FEC) and 1wt% ethylene carbonate (VC) as additives, and assembled into a CR2032 button cell, abbreviated as SiC950@CMC.
[0042] The electrochemical performance of the CR2032 button cells assembled in Example 1 and Comparative Example 1 after standing at 28°C for 10 hours. The constant current charge and discharge test conditions in the Xinwei test system are: current density 0.3C (1C = 950mAg -1 );Voltage window 0.1~1.5V. Figure 2 The cycle performance of the CR2032 button batteries assembled in Example 1 and Comparative Example 1 respectively. Figure 2 It is shown in the figure that the capacity of the CR2032 button battery assembled in Comparative Example 1 is basically decayed to 677mAg after 100 cycles at a current density of 0.3C. -1 The capacity of the CR2032 button cell assembled in Example 1 remains at 744 mAg -1 , which has higher discharge capacity and better cycle stability. It can be seen that the carbon-compatible binder CMC-Py can make the silicon-carbon negative electrode show good cycle stability.
[0043] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A carbon-compatible binder for a silicon-carbon negative electrode of a lithium-ion battery, characterized in that: The carbon-compatible binder is abbreviated as CMC-Py, which is prepared by dissolving sodium carboxymethyl cellulose in a phosphate buffer solution, then adding N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide to activate the carboxyl group of the sodium carboxymethyl cellulose, and finally adding 1-pyrenemethylamine hydrochloride solution, and reacting under N2 stirring at room temperature.
2. The carbon-compatible binder for the silicon-carbon negative electrode of a lithium-ion battery according to claim 1, characterized in that: The molar ratio of the sodium carboxymethyl cellulose and the 1-pyrenemethylamine hydrochloride in the 1-pyrenemethylamine hydrochloride solution is (2-4):1; the concentration of the 1-pyrenemethylamine hydrochloride solution is 0.01-0.04 g / mL, and the sodium carboxymethyl cellulose is 1-2 wt% of the phosphate buffer solution; the molar ratio of the sodium carboxymethyl cellulose to the total molar ratio of N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is (1-2):
1.
3. The carbon-compatible binder for the silicon-carbon negative electrode of a lithium-ion battery according to claim 1, characterized in that: The pH of the phosphate buffer solution is 5 to 6, and the reaction time is 6 to 12 hours.
4. The carbon-compatible binder for the silicon-carbon negative electrode of a lithium-ion battery according to claim 1, characterized in that: The mass ratio of the N-hydroxysuccinimide to 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1:
1.
5. The method for preparing a carbon-compatible binder for a silicon-carbon negative electrode of a lithium-ion battery according to any one of claims 1 to 4, characterized in that: The steps include: S1. dissolving sodium carboxymethyl cellulose in phosphate buffer solution, and then adding N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide to activate the carboxyl group of sodium carboxymethyl cellulose; S2. Then, 1-pyrenemethylamine hydrochloride is added to step S1, and the mixture is stirred and reacted under N2 flow at room temperature to obtain a carbon-compatible binder.
6. A negative electrode, characterized in that The negative electrode is prepared by mixing active material silicon carbon, a conductive agent and the carbon compatible binder according to any one of claims 1 to 5, dissolving them in deionized water, mixing them thoroughly and evenly, coating them on a copper foil, and vacuum drying them.
7. The negative electrode according to claim 6, characterized in that The conductive agent is one or more of conductive carbon black, carbon nanotubes, special conductive carbon black or conductive graphite; the mass ratio of the active material silicon carbon, the conductive agent and the carbon compatible binder is (7-8):(1-2):1; the vacuum drying temperature is 60-100°C, and the vacuum drying time is 10-16h.
8. Use of the negative electrode according to claim 6 or 7 in a lithium ion battery.
9. Use of the negative electrode according to claim 8 in a lithium ion battery, characterized in that: The negative electrode material of the lithium-ion battery is a silicon-carbon composite material.
Citation Information
Patent Citations
Silicon-carbon composite material for lithium ion battery and preparation method thereof
CN102891297A
Modification method and application of silicon-based binder for negative electrode material of lithium ion battery
CN112322223A
Composite binder applied to silicon-carbon negative electrode system of lithium ion battery and negative electrode material containing binder
CN115588742A
Silicon-carbon negative electrode material and preparation method thereof
CN116072855A
Thiolated polyacrylic acid water-based polymer binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of thiolated polyacrylic acid water-based polymer binder
CN116759581A
Cited By
Three-dimensional conductive network carboxymethyl cellulose composite binder and preparation method thereof
CN120173536A
Multifunctional composite binder for silicon-carbon negative electrode of lithium ion battery as well as preparation method and application of multifunctional composite binder
CN120829740A